2024
DOI: 10.1111/hex.14043
|View full text |Cite
|
Sign up to set email alerts
|

Patient versus physician preferences for lipid‐lowering drug therapy: A discrete choice experiment

Lingli Zhang,
Jiali Chen,
Zhaoliu Cao
et al.

Abstract: BackgroundThe emergence of proprotein convertase subtilisin/kexin type 9 inhibitors offered dyslipidemia patients an alternative to statins for lipid‐lowering treatment. Understanding patient and physician preferences for lipid‐lowering drugs may promote shared decision‐making and improve treatment outcomes.MethodsThis study utilized an online discrete choice experiment (DCE) to assess the relative importance (RI) of six attributes related to lipid‐lowering drugs, including frequency of administration, mode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Despite the reduction in price, our study demonstrated that spending on PCSK9 inhibitors increased one year after the policy was implemented, with a notable increase in utilization. Additionally, previous research has indicated that Chinese patients prioritize factors such as efficacy, safety, and mode of administration over OOP cost when selecting lipid-lowering drugs [ 30 ]. This change in priorities can be attributed to the NDPN policy, which has lowered the OOP cost of PCSK9 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the reduction in price, our study demonstrated that spending on PCSK9 inhibitors increased one year after the policy was implemented, with a notable increase in utilization. Additionally, previous research has indicated that Chinese patients prioritize factors such as efficacy, safety, and mode of administration over OOP cost when selecting lipid-lowering drugs [ 30 ]. This change in priorities can be attributed to the NDPN policy, which has lowered the OOP cost of PCSK9 inhibitors.…”
Section: Discussionmentioning
confidence: 99%